Case Report: A refractory unusual tetrad of overlap syndrome involving rheumatoid arthritis, Sjögren’s syndrome, autoimmune hepatitis, and type 1 renal tubular acidosis, successfully treated with a BLyS/APRIL dual inhibitor - Wang, Wenjing; Ma, Xin; Zhang, Bei; Zhang, Zhibo; Wu, Xinfeng; Jiang, Hongwei; Shi, Xiaofei (Frontiers in Immunology, 2025)
IntroductionRheumatoid arthritis (RA) and Sjögren’s syndrome (SS) are systemic autoimmune conditions. SS frequently occurs associated with RA. In patients with RA, those with SS exhibit a higher disease burden, increased disease activity, and more complex comorbidities compared with those without SS.Case reportWe report a 54-year-old female patient who was previously diagnosed with early-stage RA less than 1 year ago. She was subsequently confirmed to have SS associated with RA. Additionally, she developed multiple autoimmune comorbidities, including autoimmune hepatitis and type 1 renal tubular acidosis. The patient resisted various treatments, including immunosuppressive drugs, disease-modifying antirheumatic drugs, and anti-inflammatory small-molecule drugs. This was evidenced by poor DA28 responses, persistent laboratory abnormalities, and ongoing symptoms and signs. Finally, she responded well to Telitacicept, a BLyS/APRIL dual inhibitor.DiscussionEven in the early stage, multiple autoimmune comorbidities can exhibit high levels of disease activity and may not respond to conventional therapies. Telitacicept, the first dual inhibitor of BLyS/APRIL, has the potential to provide significant efficacy and safety for RA patients who also have overlapping SS and other autoimmune diseases that do not respond to standard treatments. The limitations included the absence of a liver biopsy and the short follow-up period.